Clinical evaluation of the failure rates of metallic brackets - Fábio Lourenço Romano; Américo Bortolazzo Correr; Lourenço Correr-Sobrinho; Maria Beatriz Borges de Araújo Magnani; Antônio Carlos de Oliveira Ruellas (University of São Paulo, 2012)
OBJECTIVES: The aim of this study was to evaluate in vivo the bonding of metallic orthodontic brackets with different adhesive systems. MATERIAL AND METHODS: Twenty patients (10.5-15.1 years old) who had sought corrective orthodontic treatment at a University Orthodontic Clinic were evaluated. Brackets were bonded from the right second premolar to the left second premolar in the upper and lower arches using: Orthodontic Concise, conventional Transbond XT, Transbond XT without primer, and Transbond XT associated with Transbond Plus Self-etching Primer (TPSEP). The 4 adhesive systems were used in all patients using a split-mouth design; each adhesive system was used in one quadrant of each dental arch, so that each group of 5 patients received the same bonding sequence. Initial archwires were inserted 1 week after bracket bonding. The number of bracket failures for each adhesive system was quantified over a 6-month period. RESULTS: The number of debonded brackets was: 8- Orthodontic Concise, 2- conventional Transbond XT, 9- Transbond XT without primer, and 1- Transbond XT + TPSEP. By using the Kaplan-Meier methods, statistically significant differences were found between the materials (p=0.0198), and the Logrank test identified these differences. Conventional Transbond XT and Transbond XT + TPSEP adhesive systems were statistically superior to Orthodontic Concise and Transbond XT without primer (p<0.05). There was no statistically significant difference between the dental arches (upper and lower), between the dental arch sides (right and left), and among the quadrants. CONCLUSIONS: The largest number of bracket failures occurred with Orthodontic Concise and Transbond XT without primer systems and few bracket failures occurred with conventional Transbond XT and Transbond XT+TPSEP. More bracket failures were observed in the posterior region compared with the anterior region.